Predictors of chronic kidney disease among HIV–infected patients on highly active antiretroviral therapy at the University of Calabar Teaching Hospital, Calabar, South-South Nigeria - Okpa HO (Dove Medical Press, 2019)
Henry Ohem Okpa,1,2 Elvis Mbu Bisong,3 Ofem Egbe Enang,2,4 Emmanuel Edet Effa,1,2 Emmanuel Monjok,3,5 Ekere James Essien51Renal Unit, Department of Internal Medicine, University of Calabar Teaching Hospital, Calabar, Nigeria; 2Department of Internal Medicine, University of Calabar, Calabar, Nigeria; 3Department of Family Medicine, University of Calabar, Calabar and University of Calabar Teaching Hospital, Calabar, Nigeria; 4Endocrine and Metabolism Unit, University of Calabar Teaching Hospital, Calabar, Nigeria; 5Institute of Community Health, University of Houston, Texas Medical Center, Houston, TX, USABackground: The burden of the people living with human immunodeficiency virus (HIV) infection and the acquired immunodeficiency syndrome (AIDS) is largely borne by communities in Sub-Saharan Africa. The rate of kidney disease is increasing amongst HIV patients and occurs more often in patients with advanced stage of the disease with lower CD4 counts and associated with a high rate of morbidity and mortality. The objective of this study is to determine the prevalence and predictors of chronic kidney disease (CKD) amongst HIV patients on highly active antiretroviral therapy (HAART) at the University of Calabar Teaching Hospital, Calabar.Materials and methods: This was a cross-sectional study that was carried out over a 4-month period from May to August 2018. In all, a total of 118 patients with HIV on HAART were recruited into the study in a consecutive manner and their serum creatinine measured with the calculation of estimated glomerular filtration rate (eGFR). Other data collected were sex, age, weight, height, body mass index (BMI), waist hip ratio (WHR), packed cell volume, CD4 count etcetera. Data collected were inputted and analyzed with SPSS version 18, and statistical significance was taken to be p<0.05.Results: There were more females (69.5%) amongst the HIV participants and the prevalence of CKD was 15.3%. The risk factors seen to be associated with CKD were lower levels of CD4 count below 200 cells/μl, lower PCV, weight, BMI, and eGFR. Also, higher levels of WHR and creatinine were associated with CKD. Factors directly correlated with CKD were weight, BMI and CD4 count levels, while creatinine level was inversely correlated with CKD. However, a logistic regression model showed only creatinine to be a predictor of CKD.Conclusion: HIV patients on antiretroviral therapy, mainly the highly active antiretroviral therapy (HAART) have a relatively high prevalence of CKD of 15.3% and high level of serum creatinine was predictive of CKD in the logistic regression model in our study.Keywords: predictors, chronic kidney disease, HIV, South – South, Nigeria